2004
DOI: 10.1111/j.1540-8159.2004.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effectiveness of Dual Site Left Ventricular Cardiac Resynchronization Therapy in a Patient with Congestive Heart Failure

Abstract: This article describes a case of cardiac resynchronization therapy (CRT) performed with dual site left ventricular pacing. The main clinical and functional long-term results are in agreement with the most recent data regarding traditional CRT. Furthermore, this innovative pacing modality allowed optimal inter- and intraventricular resynchronization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Pappone et al [11] found that this mode of stimulation was superior to singlesite left ventricular pacing in terms of acute hemodynamic performance of the ventricle and its electrical synchrony. Until very recently, the only data on triple-site biventricular pacing came from anecdotal case-reports, which suggested that this type of stimulation can improve clinical status and suppress ventricular arrhythmias in HF patients [12][13][14]. In our previous study we demonstrated that dual left-single right cardiac resynchronization is a safe method and can be performed successfully in the majority of CRT candidates [7].…”
Section: Discussionmentioning
confidence: 95%
“…Pappone et al [11] found that this mode of stimulation was superior to singlesite left ventricular pacing in terms of acute hemodynamic performance of the ventricle and its electrical synchrony. Until very recently, the only data on triple-site biventricular pacing came from anecdotal case-reports, which suggested that this type of stimulation can improve clinical status and suppress ventricular arrhythmias in HF patients [12][13][14]. In our previous study we demonstrated that dual left-single right cardiac resynchronization is a safe method and can be performed successfully in the majority of CRT candidates [7].…”
Section: Discussionmentioning
confidence: 95%
“…Sassara et al (20) described a patient presenting with permanent AF and a VVI pacemaker implanted for slow ventricular rate who underwent CRT with 2 leads implanted on the postero-basal and antero-lateral epicardial LV surface, respectively, and an RV lead implanted transvenously. At 3 months of follow-up, a clinical improvement as well as a significant reduction in LV volumes was observed with 3-V pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested the feasibility of triple‐site ventricular pacing with both dual‐RV and dual‐LV configurations . Lenarczyk et al.…”
Section: Discussionmentioning
confidence: 99%